JUSTIFICATION OF THE RECYCLING OF NATURAL RUBBER PRODUCTION WASTE FOR THE PRODUCTION OF LATEX ENR - Карнаушенко, Дмитро; Зибайло, Сергій; Ведь, Віктор; Стовпник, Олександр (SWorldJournal, 2024)
The article establishes that the recycling of NR production waste is a promising area of research. Modern technologies for obtaining epoxidized natural rubber latex were considered as a method of processing NR waste. A method for calculating the process